2018
DOI: 10.1007/s11024-018-9356-2
|View full text |Cite
|
Sign up to set email alerts
|

Docility as a Primary Virtue in Scientific Research

Abstract: Scientific epistemology is a topic that has sparked centuries of philosophical discourse. In particular, understanding the role that scientists play in the creation and perpetuation of scientific knowledge is a subject that continues to be hotly debated. A relative new-comer to scientific epistemology is the field of virtue epistemology, which positions knowledge creation as integrally linked to specific character traits held by the scientist. Positioning scientific research as a distinct practice, virtue epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This pattern of change in use over time and transition from informal use to more professional undertakings is affirmed by findings from Veletsianos, Johnson and Belikov (2019). Overall, this study demonstrated how the need for professional development motivated me to seek out opportunities using Twitter and that this professional development journey has taken several years which I believe is due to persistence and an open mind to learning (Bezuidenhout, Ratti, Warne & Beeler, 2019). This paper's potential contribution to scholarship and practice must be taken with care when generalizing its findings.…”
Section: Discussionsupporting
confidence: 53%
“…This pattern of change in use over time and transition from informal use to more professional undertakings is affirmed by findings from Veletsianos, Johnson and Belikov (2019). Overall, this study demonstrated how the need for professional development motivated me to seek out opportunities using Twitter and that this professional development journey has taken several years which I believe is due to persistence and an open mind to learning (Bezuidenhout, Ratti, Warne & Beeler, 2019). This paper's potential contribution to scholarship and practice must be taken with care when generalizing its findings.…”
Section: Discussionsupporting
confidence: 53%
“…4 Also see (Aranzadi 2013, p. 491). 5 (Boniolo and Fiore 2010;Bezuidenhout et al 2018) Concerning codes of conduct, see (Kaptein 2010). 6 (Rawls 1999, p. 11) Much of Rawls' discussion of institutions can be found on pages 171-346.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…This perspective contrasts to studies that deal in a more abstract manner with free-floating ‘epistemic virtues’ ( Van Dongen & Paul, 2017 , pp. 1–10) like objectivity ( Daston & Galison, 2007 ) or docility ( Bezuidenhout et al, 2019 ).…”
Section: Studies Of Academic Training: a Reviewmentioning
confidence: 99%